Brand Elements Lead to Brand Equity: Differentiate or Die - Farhana, Mosarrat (Information Management and Business Review, 2012)
The aim of this paper is to discuss brand elements and to explore its contribution to brand equity based on some relevant research reviews and some examples of prominent brands where brand elements have played a significant role to reach consumer’s head and heart. Brand is a combination of name, symbol or design, which creates a distinctive identity to consumers within a crowd of choices through its different brand elements. A distinctive or unique offering as well as get-up of a brand is the primary key of survival from the immature death in competition. Differentiating approach of different brand elements always cause a high level of brand awareness and familiarity among target consumers and later on individually or collectively, brand elements work as clue to consumers to recall and recognize the brand. Proper integration of both strong and weak brand elements of a brand contribute to brand equity, which has been focused here through some literature reviews.